Outcomes of paediatric patients with B-cell acute lymphocytic leukaemia with ABL-class fusion in the pre-tyrosine-kinase inhibitor era: a multicentre, retrospective, cohort study - den Boer, Monique L; Cario, Gunnar; Moorman, Anthony V; Boer, Judith M; de Groot-Kruseman, Hester A; Fiocco, Marta; Escherich, Gabriele; Imamura, Toshihiko; Yeoh, Allen; Sutton, Rosemary; Dalla-Pozza, Luciano; Kiyokawa, Nobutaka; et al. (The Lancet. Haematology, 2021)
BACKGROUND: ABL-class fusion genes other than BCR-ABL1 have been identified in approximately 3% of children with newly diagnosed acute lymphocytic leukaemia, and studies suggest that leukaemic cells carrying ABL-class fusions can be targeted successfully by tyrosine-kinase inhibitors. We aimed to establish the baseline characteristics and outcomes of paediatric patients with ABL-class fusion B-cell acute lymphocytic leukaemia in the pre-tyrosine-kinase inhibitor era. METHODS: This multicentre, retrospective, cohort study included paediatric patients (aged 1-18 years) with newly diagnosed ABL-class fusion (ABL1 fusion-positive, ABL2 fusion-positive, CSF1R fusion-positive, and PDGFRB fusion-positive) B-cell acute lymphocytic leukaemia enrolled in clinical trials of multidrug chemotherapy done between Oct 3, 2000, and Aug 28, 2018, in which tyrosine-kinase inhibitors had not been given as a first-line treatment. Patients from 14 European, North American, and Asia-Pacific study groups of the Ponte di Legno group were included. No patients were excluded, and patients were followed up by individual study groups. Through the Ponte di Legno group, we collected data on the baseline characteristics of patients, including IKZF1, PAX5, and CDKN2A/B deletion status, and whether haematopoietic stem cell transplantation (HSCT) had been done, as well as treatment outcomes, including complete remission, no response, relapse, early death, and treatment-related mortality, response to prednisone, and minimal residual disease (MRD) at end of induction therapy. 5-year event-free survival and 5-year overall survival were estimated by use of Kaplan-Meier methods, and the 5-year cumulative incidence of relapse was calculated by use of a competing risk model. FINDINGS: We identified 122 paediatric patients with newly diagnosed ABL-class fusion B-cell acute lymphocytic leukaemia (77 from European study groups, 25 from North American study groups, and 20 from Asia-Pacific study groups). 64 (52%) of 122 patients were PDGFRB fusion-positive, 40 (33%) were ABL1 fusion-positive, ten (8%) were CSF1R fusion-positive, and eight (7%) were ABL2 fusion-positive. In all 122 patients, 5-year event-free survival was 59·1% (95% CI 50·5-69·1), 5-year overall survival was 76·1% (68·6-84·5), and the 5-year cumulative incidence of relapse was 31·0% (95% CI 22·4-40·1). MRD at the end of induction therapy was high (≥10-2 cells) in 61 (66%) of 93 patients, and most prevalent in patients with ABL2 fusions (six [86%] of 7 patients) and PDGFRB fusion-positive B-cell acute lymphocytic leukaemia (43 [88%] of 49 patients). MRD at the end of induction therapy of 10-2 cells or more was predictive of an unfavourable outcome (hazard ratio of event-free survival in patients with a MRD of ≥10-2vs those with a MRD of <10-2 3·33 [95% CI 1·46-7·56], p=0·0039). Of the 36 (30%) of 119 patients who relapsed, 25 (69%) relapsed within 3 years of diagnosis. The 5-year cumulative incidence of relapse in 41 patients who underwent HSCT (17·8% [95% CI 7·7-31·3]) was lower than in the 43 patients who did not undergo HSCT (45·1% [28·4-60·5], p=0·013), but event-free survival and overall survival did not differ between these two groups. INTERPRETATION: Children with ABL-class fusion B-cell acute lymphocytic leukaemia have poor outcomes when treated with regimens that do not contain a tyrosine-kinase inhibitor, despite the use of high-risk chemotherapy regimens and frequent HSCT upon first remission. Our findings provide a reference for evaluating the potential benefit of first-line tyrosine-kinase inhibitor treatment in patients with ABL-class fusion B-cell acute lymphocytic leukaemia. FUNDING: The Oncode Institute, Pediatric Cancer Foundation Rotterdam, Dutch Cancer Society, Kika Foundation, Deutsche Krebshilfe, Blood Cancer UK, Associazione Italiana per la Ricerca sul Cancro, Cancer Australia, National Cancer Institute, National Institute of Health, and St Baldrick's Foundation.
Keywords: fúzní onkogenní proteiny; alografty; následné studie; lidé; mladiství; inhibitory proteinkinas; Infant; Female; dítě; Adolescent; Humans; tyrosinkinasy; Follow-Up Studies; Progression-Free Survival; pre-B-buněčná leukemie; Hematopoietic Stem Cell Transplantation; Allografts; protoonkogenní proteiny c-abl; předškolní dítě; doba přežití bez progrese choroby; Child, Preschool; přežití bez známek nemoci; mužské pohlaví; transplantace hematopoetických kmenových buněk; Disease-Free Survival; ženské pohlaví; Protein Kinase Inhibitors; Male; Oncogene Proteins, Fusion; Child; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Protein-Tyrosine Kinases; Proto-Oncogene Proteins c-abl; kojenec